Decision Support System For Recognizing Student Interests in School Extracurricular Fields With Topsis Method - Nasution, Ismail Saleh (Al'Adzkiya, 2022)
So far, the condition of children's development during the school period tends to choose the wrong choice or just follow along in choosing something, especially in terms of choosing an extracurricular field at school, which is basically not due to their own desire or interest in choosing an extracurricular field. So it is necessary to build a system that can help provide appropriate and appropriate decisions to help determine in recognizing the extracurricular interests of students.One method that can be used for decision support systems is to use the TOPSIS method. In this research, a case will be raised, namely finding the best alternative based on predetermined criteria using the TOPSIS method to perform calculations on the case. This method was chosen because it is able to select the best alternative from a number of alternatives, in this case the intended alternative is the extracurricular field based on the specified criteria. The results of the implementation process can sort alternatives from the largest value to the smallest value.